The Diagnostic Accuracy of IgG Avidity Testing for Differentiating Acute from Chronic Toxoplasmosis in Pregnant Women: A Meta-Analysis - Hermalina Sherli Utami; Rohayat Bilmahdi; Fadrian (HM Publisher, 2025)
Background: Differentiating acute from chronic Toxoplasma gondii infection during pregnancy is a critical diagnostic challenge. Persistent Immunoglobulin M (IgM) antibodies create ambiguity, complicating clinical management. The IgG avidity test serves as a key tool to estimate infection timing. This meta-analysis aimed to systematically evaluate and quantify the diagnostic accuracy of the IgG avidity test for identifying acute toxoplasmosis in pregnant women. Methods: A systematic literature search was conducted across PubMed, Scopus, Web of Science, EMBASE, and LILACS for studies published between January 2015 and December 2025 evaluating the IgG avidity test's diagnostic accuracy in pregnant women. Included studies required data for a 2x2 contingency table. The QUADAS-2 tool was used for bias assessment. A bivariate random-effects model was used to pool sensitivity, specificity, likelihood ratios (PLR, NLR), and the diagnostic odds ratio (DOR). Results: Seven studies, comprising 1,250 pregnant women, were included. The pooled sensitivity was 0.96 (95% Confidence Interval [CI]: 0.92–0.98), and the pooled specificity was 0.97 (95% CI: 0.94–0.99). The pooled PLR was 32.5 (95% CI: 15.1–69.8), the NLR was 0.04 (95% CI: 0.02–0.08), and the DOR was 785 (95% CI: 289–2134). The area under the SROC curve was 0.99 (95% CI: 0.97–1.00). Substantial heterogeneity was observed across studies. A sensitivity analysis excluding one study with a high risk of bias did not significantly alter the results, and Deeks' test showed no evidence of publication bias (p=0.21). Conclusion: The IgG avidity test demonstrated excellent pooled diagnostic accuracy for differentiating acute from chronic toxoplasmosis in pregnancy. However, significant heterogeneity across studies underscores that a single performance estimate is not universally applicable. The test is a powerful tool for resolving diagnostic uncertainty, but results must be interpreted based on assay-specific performance and in the context of the complete clinical picture.